Alisma canaliculatum ethanol extract suppresses inflammatory responses in LPS-stimulated macrophages, HCl/EtOH-induced gastritis, and DSS-triggered colitis by targeting Src/Syk and TAK1 activities. (12th June 2018) - Kim, Han Gyung; Kim, Mi-Yeon; Cho, Jae Youl
Abstrac: Ethnopharmacological relevance: Alisma canaliculatum A.Braun & C.D.Bouché, distributed in Korea, Japan, China, and Taiwan, is a traditional medicine. In particular, the stem and root of Alisma canaliculatum A.Braun & C.D.Bouché are prescribed to relieve various inflammatory symptoms resulting from nephritis, cystitis, urethritis, and dropsy. Aim of study: However, the curative mechanism of Alisma canaliculatum A.Braun & C.D.Bouché with respect to inflammatory symptoms is poorly understood. In this study, the curative roles of this plant in various inflammatory conditions as well as its inhibitory mechanism were aimed to examine using an ethanol extract (Ac-EE). Materials and methods: Anti-inflammatory effects of Ac-EE were evaluated in lipopolysaccharide (LPS)-induced macrophages in vitro and HCl/EtOH-stimulated mouse model of gastritis and DSS-treated mouse model of colitis. To determine the potentially active anti-inflammatory components in this extracts, we employed HPLC. We also used kinase assays, reporter gene assay, immunoprecipitation analysis and target enzyme overexpressing cell analysis to analyze the molecular mechanisms and the target molecules. Results: This extract dose-dependently inhibited the production of nitric oxide (NO) and prostaglandin E2 (PGE2 ) from RAW264.7 cells and peritoneal macrophages activated by lipopolysaccharide (LPS). Additionally, Ac-EE ameliorated inflammatory symptoms resulting from gastritis and colitis. Ac-EE down-regulated the mRNA levels of inducible NO synthase (iNOS), tumor necrosis factor (TNF)-α, and cyclooxygenase-2 (COX-2). Ac-EE also blocked the nuclear translocation of nuclear factor (NF)-κB and activator protein (AP)− 1 in LPS-stimulated RAW264.7 cells. By analyzing the target signaling molecules activating these transcription factors, we found that Src and Syk, as well as molecular association between TAK1 and mitogen-activated protein kinase kinase 4/7 (MKK4/7), were targeted by Ac-EE. Conclusions: Our data suggest that the Ac-EE NF-κB/AP-1-targeted anti-inflammatory potential is mediated by suppression of Src and Syk as well as the complex formation between TAK1 and its substrate proteins MKK4/7. Graphical abstract: fx1